Finding the Breech: Influence of Breech Presentation on Mode of Delivery Based on Timing of Diagnosis, Attempt at External Cephalic Version, and Provider Success With Version. Issue 2 (June 2018) - Andrews, S.; Leeman, L.; Yonke, N.
Abstract : ( Birth . 2017;44(3):222–229) Breech presentation accounts for 10% to 15% of cesarean deliveries in the United States. Cesarean delivery presents maternal risks and risk for future pregnancies. External cephalic version has a 60% success rate and is effective in decreasing cesarean deliveries. Optimal timing for external cephalic version is 36 to 37 weeks. At a later gestational age, advanced labor or rupture of membranes may prevent external cephalic version. This study investigated the connection between gestational age when breech presentation is diagnosed and the likelihood of a vaginal delivery, hypothesizing that the likelihood of vaginal delivery and external cephalic version would decrease if there was a failure to diagnose breech presentation before 38 weeks' gestation.